Pengaruh Manajemen Laba dan Struktur Modal Terhadap Nilai Perusahaan (Studi Kasus Pada Perusahaan Asuransi yang Terdaftar di BEI Periode 2015-2019) - Siti Sa'adah Nurul Jannah; Daryanto Hesti Wibowo (Institut Ilmu Sosial dan Manajemen Stiami, 2021)
The aim of this study is to determine the effect earnings management and capital structure on firm’s Value, The type of this Eksplanasi Research and used the secondary data which were obtained by the documentation tehnique, this study observed Asurance Companies. listed in Indonesia Stock Exchange period of 2015-2019, the sampel was obtained by purposive sampling method. The analysi data used inthis study was data panel regresssion analysis. The result of this analysis states that earnings managemen and capital structure effec firm’s Value simultaneously. Partially, variabel that no effect the firm’s Value are earnings management and capital structure